Optimasi Injeksi Photovoltaic Distributed Generations (PVDG) Menggunakan Metode Algoritma Genetika - Muammar Zainuddin; Hadi Suyono; Harry Soekotjo Dachlan (Fakultas Teknik, Universitas Brawijaya, 2014)
The best solution of the problem of electrical energy crisis in Indonesia, with the utilization of renewable energy sources that are environmentally friendly, economical, sustainable, and technically easily to implemented. The model system proposed in this paper is the Photovoltaic Distributed Generation (PVDG). This paper discuss modeling PVDG by searching injection placement and size us Genetic Algorithm. Optimization is done with the concept of the four scenarios increase the value of the injection. The scenario used was an increase in injection rate + 10%, + 20% + 30% and + 40% from the initial source of generation. The obtained results show the system ideal conditions is contained in the scenario-4. The results found that 8 locations with a variety of sizing power. PVDG scenario-4 modeling results show the ability of the system to minimize power loss from 13,15% to 1,30% and the highest voltage drop -25% to -8,5% of nominal voltage.Index Terms—Photovoltaic, Distributed Generations, PVDG, Genetic Algorithm.